Paradoxes of Jewish Firstness - Gans, Eric Lawrence (2021)
for Adam Katz In a response to Chronicle 705 ("The Jews"), Adam suggested that the uniqueness of the Jews should be "thought in terms of some particular, ongoing, historical relationship between the Jews and mimesis." This particularity is, in a word, what I have been calling firstness. My use of the term is something...